CYTOKINES AND PROTEINS OF THE EXTRACELLULAR MATRIX IN THE BLOOD OF RATS OF DIFFERENT AGES AFTER FILLING THE DEFECT IN THE FEMORAL METAPHYSIS WITH ALLOGENEIC BONE IMPLANTS SATURATED WITH MESENCHYMAL STEM CELLS - Petro Vorontsov; Frida Leontieva; Vladyslav Tulyakov; Igor Husakov (Acta Medica Leopoliensia)
Mesenchymal stem cells (MSCs) are used for the improvement of the repair of allografts.